2006
DOI: 10.3200/aeoh.61.5.209-213
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Hazards of Sachet Water in Nigeria

Abstract: The authors assessed sachet water samples sold in Eastern Nigeria. Using an atomic absorption spectrophotometer, they analyzed levels of lead, cadmium, copper, and nickel. They also analyzed other parameters, such as nitrates, sulfates, chlorides, salinity, total hardness, biological oxygen demand, total dissolved solids, and pH level. Lead levels ranged from 0.002 to 0.036 mg/L in the samples; 5 samples (12.2%) had lead levels above the maximum contaminant level (MCL; 0.015 mg/L). Lead was not detectable in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Because many sachet producers are small-scale cottage industries, Ghanaian regulatory agencies, such as the Food and Drugs Board and Ghana Standards Board, have had difficulty tracking the sachet industry's rapid growth and ensuring quality control. Recent research on sachet water has primarily focused on sub-standard quality and potential disease transmission in Ghana (Addo et al, 2009; Ampofo et al, 2007; Dodoo et al, 2006; Kwakye-Nuako et al, 2007; Obiri-Danso et al, 2003), and Nigeria (Adenkunle et al, 2004; Ejechi and Ejechi, 2008; Ifeanyi et al, 2006; Nwosu and Ogueke, 2004; Olaoye and Onilude, 2009; Onifade and Ilori, 2008; Orisakwe et al, 2006; Oyedeji et al, 2010), with some elaboration on health impact. Although not every study has found sachet water quality to be troublesome (Egwari et al, 2005; Olowe et al, 2005), there is generally a bias toward the publication of negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…Because many sachet producers are small-scale cottage industries, Ghanaian regulatory agencies, such as the Food and Drugs Board and Ghana Standards Board, have had difficulty tracking the sachet industry's rapid growth and ensuring quality control. Recent research on sachet water has primarily focused on sub-standard quality and potential disease transmission in Ghana (Addo et al, 2009; Ampofo et al, 2007; Dodoo et al, 2006; Kwakye-Nuako et al, 2007; Obiri-Danso et al, 2003), and Nigeria (Adenkunle et al, 2004; Ejechi and Ejechi, 2008; Ifeanyi et al, 2006; Nwosu and Ogueke, 2004; Olaoye and Onilude, 2009; Onifade and Ilori, 2008; Orisakwe et al, 2006; Oyedeji et al, 2010), with some elaboration on health impact. Although not every study has found sachet water quality to be troublesome (Egwari et al, 2005; Olowe et al, 2005), there is generally a bias toward the publication of negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the primary sources of lead exposure that Nigerians are exposed to, there seems to be recent studies and reports revealing the presence of lead in sundry consumables in Nigeria such as herbal remedies [40], beverages [41, 42], and drugs [43] that put the vulnerable population at risk of lead poisoning. To be exposed to lead from cosmetics may raise another concern.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is difficult to contaminate bottled water after packaging and there is yet no substantial evidence that E.coli multiplies appreciably in drinking water, the bottled samples may have been contaminated at some point during the production process, thus pointing to poor quality assurance process of the factories. 7,35 The sachet water contamination might have occurred at any point during the production, distribution, or storage process by virtue of its packaging. The presence of E coli in the packaged water samples indicates that the population of Nnewi is at risk of waterborne diarrheal diseases, especially in the absence of any further treatment of this drinking water source.…”
Section: Discussionmentioning
confidence: 99%
“…This result coincides with that obtained from a study carried out in South Eastern Nigeria by Orisakwe and colleagues. 7,35 The affected water samples were produced by factories located in Nnewi. This finding could be explained in either of two ways: water production factories in Nnewi use lead pipe systems leading to corrosion by acidic water or the lead produced by industries in Nnewi might have leached into the water source.…”
Section: Discussionmentioning
confidence: 99%